2015
DOI: 10.1016/j.ajpath.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Human Decidual Cell–Expressed FKBP51 May Promote Labor-Related Functional Progesterone Withdrawal

Abstract: Sustained plasma progesterone (P4) levels suggest initiation of human term labor by functional P4 withdrawal, reflecting reduced progesterone receptor (PR) and/or glucocorticoid receptor (GR) expression or activity. The steroid-induced immunophilin cochaperone FKBP51 inhibits PR- and GR-mediated transcription, suggesting a labor-initiating role. Gestational age-matched decidual sections were immunostained for FKBP51 and decidual cell (DC) and interstitial trophoblast (IT) markers, vimentin and cytokeratin, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
2
8
0
1
Order By: Relevance
“…The failure of such therapy, coupled with observations that PR antagonist therapy ± prostaglandins induce labor at all gestational ages (51), indicates that functional P4 withdrawal mediated at the level of the PR triggers human labor. This hypothesis is further supported by our previous findings that term labor is associated with reduced decidual PR and increased decidual FKBP51 expression (20,31) and that chorioamnionitis and abruption, major etiologies of early PTB, are associated with reduced PR expression (22,24). We now demonstrate that idiopathic and stress-associated PTB, major causes of late PTB, are also triggered by functional P4 withdrawal, albeit mediated through increased FKBP51 expression.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The failure of such therapy, coupled with observations that PR antagonist therapy ± prostaglandins induce labor at all gestational ages (51), indicates that functional P4 withdrawal mediated at the level of the PR triggers human labor. This hypothesis is further supported by our previous findings that term labor is associated with reduced decidual PR and increased decidual FKBP51 expression (20,31) and that chorioamnionitis and abruption, major etiologies of early PTB, are associated with reduced PR expression (22,24). We now demonstrate that idiopathic and stress-associated PTB, major causes of late PTB, are also triggered by functional P4 withdrawal, albeit mediated through increased FKBP51 expression.…”
Section: Discussionsupporting
confidence: 87%
“…We previously showed decreased PR and increased FKBP51 expression in the nuclei of decidual cells in placental sections obtained from laboring versus nonlaboring women at term (20,31), suggesting a contributing role for FKBP51 in mediating decidua-specific functional P4 withdrawal during parturition. To investigate if these molecular changes also occur in decidua obtained from iPTB specimens, we assessed FKBP5 and PGR expression by qPCR in decidua basalis specimens obtained from women with iPTB compared with two control groups: 1) negative control-GA-matched women with elective PTB for placenta accreta (PA) or indicated PTB for preeclampsia (PE) or 2) positive control-women in labor at term.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, based on our researches, no other studies have been conducted for evaluation of FKBP51 gene expression in endometrial tissue of women with gynecological problems to be compared with our study results. Only one study showed that a higher level of FKBP51 gene expression in decidual cells of pregnant women facilitates their labor process by reducing sensitivity of these cells to progesterone, indicating its contribution to progesterone signaling pathway and response of target tissues to progesterone (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of progesterone hormone, FKBP51 and FKBP52 act as progesterone receptor co-chaperons. These immunophilins have a similar structure, but FKBP52 increases the affinity of PR for its ligand while FKBP51 decreases this affinity, thereby reducing the response of target tissue to this hormone (17,(23)(24). Studies showed that Fkbp52 null female mice are infertile due to endometrial receptivity defects, and their inability to sustain pregnancy was related to progesterone hormone resistance (25)(26).…”
Section: Introductionmentioning
confidence: 96%